Wind Shear Stress Acting on Water Surface - KIM, Byungill; MIZUTANI, Natsuki (Journal of the Visualization Society of Japan, 2007)
This study investigated about the continuity of momentum flux through an air-water interface. We conducted to measure air-flow and water-flow very close to a water surface in a wind wave tank using PIV technique. To evaluate of the continuity of momentum flux calculating from the friction velocity was very difficult, because we could not detect exact a mean water level to fit a log-law profile for the experimental data. The viscous stress affected not only the viscous sub layer but also the turbulent boundary layer. The ratio of the viscous stress in water-flow is from several percent to about ten percent. We deduced that the continuity of momentum flux calculating from the total stress was strongly affected by three-dimensional turbulent water-flow.